YouTube vs television in media convergence era: case study study on tonight show program presented by Net Mediatama - Estavita Chantik Pembayun (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2022)
The use of the internet has become a habit among millennials lately. The products of these two media are television and YouTube. Presentation of content that is considered almost the same, namely using audio-visual media, YouTube is considered to be a new medium that will shift and even replace the existence of the television industry. In 2020, We are Social analysis said the number of YouTube users reached 2 billion each month. This has a significant impact on television, one of which is NET (News and Entertainment Television) that owned by PT NET Mediatama. The increasing number of YouTube viewers compared to declining television, NET experienced a decline in revenue in 2020, due to a continuous decrease in audience ratings with the number of sponsors obtained. As a conventional media, NET now has to compete with YouTube. The program that is the focus of this research is the Tonight Show, where the program is broadcast hybridly in terrestrial form and exclusively on YouTube streaming. The research was conducted using a constructivist paradigm and a qualitative approach with a case study method. Interviews with assistant producers of the Tonight Show became primary data and published interviews, media content and literature that examined the convergence of communication media and industry became secondary data. Based on research findings from a business point of view, convergence in the television industry can open up new professional opportunities, such as providing opportunities for television media managers to expand public choice, as has been implemented by the Tonight Show program with the Tonight Show Premiere. Even though YouTube viewers in Indonesia are increasing, the existence of the television industry still has its place, because exposure to television content can be felt by more people compared to YouTube, because not everyone can access the internet, especially in Indonesia.